Association of breed and histopathological grade in canine mast cell tumours. (19th May 2016) - Mochizuki, H.; Motsinger‐Reif, A.; Bettini, C.; Moroff, S.; Breen, M.
Abstract: The aim of this study was to evaluate the relationship between breed and the histopathological grade of canine mast cell tumours (MCTs). A retrospective survey of pathology data of 9375 histopathologically confirmed diagnoses of cutaneous MCTs in the US was evaluated in the context of breed prevalence in over two million registered purebred dogs. Association of histopathological grade with breed, age, sex and spay/neuter status was assessed. The data indicate that the proportion of high‐grade tumours increases with advancing age, and that male and intact dogs have increased odds of developing high‐grade tumours. A significant difference in the proportion of high‐grade tumours between breeds was detected. The Pug was at significantly increased risk of developing low/intermediate‐grade tumours, but not high‐grade tumours, resulting in preponderance of less aggressive MCTs in this breed. The results of this study suggest a genetic association for the development of high‐grade MCTs.